Induction of Brain Tumors by the Archetype Strain of Human Neurotropic JCPyV in a Transgenic Mouse Model - Luis Del Valle; Kamel Khalili (Viruses, 2021)
JC Virus (JCPyV), a member of the Polyomaviridiæ family, is a human neurotropic virus with world-wide distribution. JCPyV is the established opportunistic infectious agent of progressive multifocal leukoencephalopathy, a fatal demyelinating disease, which results from the cytolytic infection of oligodendrocytes. Mutations in the regulatory region of JCPyV determine the different viral strains. Mad-1 the strain associated with PML contains two 98 base pair repeats, whereas the archetype strain (CY), which is the transmissible form of JCPyV, contains only one 98 tandem with two insertions of 62 and 23 base pairs respectively. The oncogenicity of JCPyV has been suspected since direct inoculation into the brain of rodents and primates resulted in the development of brain tumors and has been attributed to the viral protein, T-Antigen. To further understand the oncogenicity of JCPyV, a transgenic mouse colony containing the early region of the archetype strain (CY), under the regulation of its own promoter was generated. These transgenic animals developed tumors of neural crest origin, including: primitive neuroectodermal tumors, medulloblastomas, adrenal neuroblastomas, pituitary tumors, malignant peripheral nerve sheath tumors, and glioblastomas. Neoplastic cells from all different phenotypes express T-Antigen. The close parallels between the tumors developed by these transgenic animals and human CNS tumors make this animal model an excellent tool for the study of viral oncogenesis.